2007
DOI: 10.1111/j.1741-2358.2007.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic evaluation of masseter and anterior temporalis muscles in rest position of edentulous patients with temporomandibular disorders, before and after using complete dentures with sliding plates

Abstract: The sliding plates allowed the process of neuromuscular deprogramming, contributing to muscular balance of the masticatory system, and are therefore indicated to be used before the fabrication of definitive complete dentures in patients with TMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
2
20
1
3
Order By: Relevance
“…10 The 11 This study evidenced more force in the masseter muscles of men, which the authors attributed to muscle size, although this gender-related asymmetry has not been observed in previous studies. 6 Therefore, in confirmation of the conclusions of the authors and others, 5,[7][8][9] it seems that the muscular electrical activity recorded by surface EMG provides a useful and reproducible functional guide to mandibular mechanics in healthy subjects. EMG can assist in understanding variations in muscular behavior 8 in patients with prostheses, malocclusion, craniomandibular syndromes or muscular diseases.…”
supporting
confidence: 58%
See 2 more Smart Citations
“…10 The 11 This study evidenced more force in the masseter muscles of men, which the authors attributed to muscle size, although this gender-related asymmetry has not been observed in previous studies. 6 Therefore, in confirmation of the conclusions of the authors and others, 5,[7][8][9] it seems that the muscular electrical activity recorded by surface EMG provides a useful and reproducible functional guide to mandibular mechanics in healthy subjects. EMG can assist in understanding variations in muscular behavior 8 in patients with prostheses, malocclusion, craniomandibular syndromes or muscular diseases.…”
supporting
confidence: 58%
“…La evaluación electromiográfica ha sido utilizada por diferentes autores en los últimos años no solo para el conocimiento de la mecánica mandibular: 3-6 estudios centrados en la actividad de reposo, actividad en el esfuerzo máximo, balance muscular y simetría muscular sino también para el conocimiento de las alteraciones que producen numerosos síndromes craneomandibulares de origen muscular: 7,8 …”
unclassified
See 1 more Smart Citation
“…16 Even with the use of a Lucia jig for 30 minutes, no statistically significant changes were observed in the muscle activation patterns over time. The activation pattern eventually increased or decreased, but the numerical pattern changes were small.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to bone and muscular changes in the stomatognathic system of individuals with malocclusion. [1011] In habitual gum chewing and dental clenching, there was a statistically significant difference in the activities before and after SARME ( P < 0.01). In mouth opening and closing and at rest, just for the right temporal muscle, the data was statistically significant ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%